(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA), also known as Mahatma Gandhi National Rural Employment Guarantee Scheme (MNREGS) is Indian legislation enacted on August 25, 2005. The MGNREGA provides a legal guarantee for one hundred days of employment in every financial year to adult members of any rural household willing to do public work-related unskilled manual work at the statutory minimum wage.This scheme is a paradigm shift in employment generation in rural India. Presently, this scheme is also developing the natural resources in rural areas with many activities like Watershed development, Afforestation, Rejuvenation of traditional water bodies (Canal, Ponds, Step well etc.), Development of community land, Water conservation and Water-harvesting, Development of livestock infrastructure (piggery, fishery, goat shelters etc.), Horticulture development etc.The concept of “Economic convergence” is that we have to mobilize these natural resources to generate income for rural population. The government labels 30 per cent of India’s landmass as “wasteland” and wants to open it up for industry and agriculture. This concept will help the Gram-Panchayats to make self-sufficient.